Hubungan Angka Kejadian Metabolik Sindrom dengan Dislipedimia: Studi Literatur - Abrori, Amiril; Rahmawati, Febtarini; Listyawati, Agusniar Furkani (Institute for Research and Community Services (LPPM) of University of Wijaya Kusuma Surabaya, 2023)
Introduction: Metabolic syndrome is a composite of multiple cardiovascular disorders characterized by abdominal/central obesity, increased blood sugar, blood pressure, triglycerides, and decreased high-density lipoprotein (HDL). As a result of disorders caused by Metabolic Syndrome which causes one of the diseases Dyslipidemia. The purpose of this study was to determine the relationship between the incidence of Metabolic Syndrome and Dyslipidemia. Method: This study used a literature study research method which was carried out by collecting data through literature searches or electronic-based literature reviews using internet media. Result: In this literature review, the authors cite thirty journals consisting of eighteen national journals and twelve international journals. Twenty-five journals in this study showed a correlation between the relationship between the incidence of metabolic syndrome and dyslipidemia. junk food and lack of regular exercise. Conclusion: There is a relationship between the incidence of metabolic syndrome and dyslipidemia. Keywords: Incidence Rate, Metabolic Syndrome, Dyslipidemia